The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s0103-97332006000300027
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotransport in Al xGa x-1As quantum wells with different potential shapes

Abstract: We compare the transport properties for triangular, parabolic and cubic quantum wells. We calculate the transport mobility for electrons belonging to the different subbands. We obtain the energy spacing between first and second subbands from the electron sheet density and compare results for different potential profiles. We find that experimental results are in quantitative agreements with our calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…The electron mobility µ is demonstrated as a function of 2D‐electron density in GaAs/Al x Ga 1 −x As QWs by considering triangular, parabolic, and cubic potential structures . It has been shown that in a wide well structure the background impurity limits the mobility . Although a great deal of efforts has been made to investigate the optical properties of the non‐square potential well structures, very few attempts have been made to study the electron transport properties of these structures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The electron mobility µ is demonstrated as a function of 2D‐electron density in GaAs/Al x Ga 1 −x As QWs by considering triangular, parabolic, and cubic potential structures . It has been shown that in a wide well structure the background impurity limits the mobility . Although a great deal of efforts has been made to investigate the optical properties of the non‐square potential well structures, very few attempts have been made to study the electron transport properties of these structures.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there is considerable interest in the study of semiconductor quantum well (QW) structures having different shapes of confinement potentials, viz., square, parabolic, graded, V‐shaped, inverse parabolic, triangular, etc., because of their applications in devices . The change in the potential profile of a quantum well affects the subband energy states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific nature of these potentials also causes dramatic change in the electrical and optical properties of the system [4,7,9]. The potentials like parabolic [1][2][3][4], triangular [5][6][7][8][9], graded [10][11][12], V-shaped [13][14][15], cubic [14,15], inverse-parabolic [16][17][18], semi-parabolic [19,20], inverse V-shaped [21], semi V-shaped [22], square-parabolic [23], Gaussian [24] etc are the examples of such systems. Light emitting diodes based on triangular-shaped QWs have more internal quantum efficiency compared to that of rectangular ones [6].…”
Section: Introductionmentioning
confidence: 99%
“…Radu et al have calculated laser-dressed states of electrons in graded QWs [10]. Magnetotransport properties of non-square QWs are studied by Mamani et al [15]. Ozturk et al have compared the linear optical absorption coefficients of parabolic with inverse parabolic QWs through the dipole moment matrix elements [16].…”
Section: Introductionmentioning
confidence: 99%